2016
DOI: 10.7231/jon.2016.27.1.023
|View full text |Cite
|
Sign up to set email alerts
|

The Review Study on Yoga, Qigong, and Taichi Interventions for Anxiety: Based on Korean Journal Articles from 2009 to 2015

Abstract: Objectives: This study was performed to investigate the research trends of physical activities interventions such as yoga, taichi, and qigong to reduce anxiety. Methods: Korean databases were searched for articles related to survey of physical activity interventions (yoga, taichi, qigong) to reduce anxiety from 2009 to 2015. Results: Fifteen articles published in Korean journals from 2009 to 2015 were retrieved. The quality of studies were generally low and characteristics of subject were not homogeneous. Spie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In this study, the Yangsaeng therapy improved physical health status, life satisfaction, and level of Yangsaeng, as well as reduced the depression for the older adults residing in nursing homes, thereby showing similar results to that of the previous studies [ 12 , 16 ]. It showed that Yangsaeng therapy had positive effects on the physical health status, depression, life satisfaction, and level of Yangsaeng of the older adults residing in nursing homes.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this study, the Yangsaeng therapy improved physical health status, life satisfaction, and level of Yangsaeng, as well as reduced the depression for the older adults residing in nursing homes, thereby showing similar results to that of the previous studies [ 12 , 16 ]. It showed that Yangsaeng therapy had positive effects on the physical health status, depression, life satisfaction, and level of Yangsaeng of the older adults residing in nursing homes.…”
Section: Discussionsupporting
confidence: 87%
“…The Korean version of the CMI showed an acceptable to good face and content validity in the previous study [ 18 ] and was standardized for Korean. At the time of the development [ 16 ], Cronbach’s α = 0.86, and reliabilities in this study were Cronbach’s α = 0.88.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…In recent years, there has been increasing interest in taichi as an exercise treatment method for various diseases [9][10][11][12][13][14][15]. According to a study conducted by Kim [16], taichi may lower sympathetic tone and increase parasympathetic tone, which may result in changes in the autonomic nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increasing interest in tai chi as an exercise treatment method for treating various diseases (9)(10)(11)(12)(13)(14)(15) . According to a study conducted by Kim (16) , tai chi may lower sympathetic tone and increase parasympathetic tone, which may affect autonomic nervous system changes.…”
Section: Introductionmentioning
confidence: 99%